Constructing and negotiating boundaries of morally acceptable alcohol use: A discursive psychology of justifying alcohol consumption. (December 2021) - Melia, Claire; Kent, Alexandra; Meredith, Joanne; Lamont, Alexandra
Highlights: There is a pervasive orientation to potential judgement regarding alcohol use. Speakers construct contrasting categories to deny being a problematic drinker. The boundary of social acceptability is locally constructed within interaction. Defining this boundary allows safe disclosures about personal drinking habits. Local constructions of social acceptability pose issues for health policy. Abstract: UK society has a complex relationship with alcohol; it is ever-present within social activities, yet alcohol problems are heavily stigmatised. As such, the nuance of acceptability is a key focus for understanding societal perceptions and understandings of alcohol. This research explored how the boundary between acceptable and problematic alcohol use was negotiated in justifying drinking behaviors. The paper draws upon data from two World Cafés and five focus groups conducted in the UK with 76 participants including 25 males and 51 females aged 18 to 82. Data was analysed using discursive psychology with a focus on how participants disclosed and accounted for alcohol consumption. The analysis highlighted two key discursive patterns: 1) Speakers created an interactionally-specific boundary of acceptable alcohol use. 2) Speakers built upon this boundary, justifying and portraying their own drinking as socially acceptable. The boundary of acceptable alcohol use was locally constructed and shifted between speakers and contexts. This locally occasioned boundary demonstrates the challenge of objective guidance - such as the UK Chief Medical Officer's unit guidelines - in relation to individualistic behaviors. Implications are discussed for how alcohol policy, health campaigns, and alcohol practitioners may consider this orientation to justifying drinking behaviors to make alcohol reduction efforts more effective.